Increased cerebral cortex activation in stroke patients during electrical stimulation of cerebellar fastigial nucleus with functional near-infrared spectroscopy - Ma, Haiyun; Zhai, Yujia; Xu, Zhen; Fan, Shengnuo; Wu, Xian; Xu, Jing; Wu, Shaoling; Ma, Chao (Frontiers in Neuroscience, 2022)
Abstract Background: Electrical stimulation of the cerebellar fastigial nucleus (FNS) has been shown to protect animals against cerebral ischemic injury. However, the changes in cortical activation as a response to FNS have not been illustrated in humans. Objective: This study aims to detect functional connectivity changes in the brain of stroke patients, and investigate the cortical activation caused by FNS through measuring the oxygenated hemoglobin concentration (HBO) in the cerebral cortex of stroke patients and healthy controls (HCs). Methods: This study recruited 20 patients with stroke and 20 HCs with all the following factors matched: age, gender and BMI. The experiment session was made up of the pre-task baseline, FNS task period, and post-task baseline. FNS task period contains 5 blocks, each block encompassing the resting state (30 s) and the FNS state (30 s). HBO signals were acquired by functional near-infrared spectroscopy (fNIRS) from the Prefrontal Cortex (PFC), the Motor Cortex (MC) and the Occipital Cortex (OC) throughout the experiment. The Pearson correlation coefficient was used to calculate the resting-state functional connectivity strength between the two groups, and the general linear model was used to calculate the activation of 39 fNIRS channels during FNS in stroke patients and HCs, respectively. Results: The coupling strength of stroke patients were significantly decreased in the following regions: right MC and left MC (t= 4.65, p= 0.0007), right MC and left OC (t= 2.93, p= 0.04), left MC and left OC (t= 2.81, p= 0.04). In stroke patients, the changes in cerebral oxygenated hemoglobin (∆HBO) among 12 channels (CH) in the bilateral PFC and bilateral MC regions were significantly increased during the FNS state (FDR corrected p ＜ 0.05) compared with the resting state. In HCs, only 1 channel was increased (FDR corrected p ＜ 0.05) in the left PFC during FNS. Conclusion: By using the FNS and fNIRS techniques, the characteristics of functional connectivity were found to decrease in stroke patients. It was also noticed that FNS activates the PFC and MC regions. These findings may help to guide functional rehabilitation in stroke patients.